Abordagens híbrida e clil invertida : tensões e diálogos entre ensino e educação linguística - Lima, Sebastião (2017)
The study aims to reflect on the potential and limitations of the blended learning approach for language education through the Content and Language Integrated Learning (CLIL) approach in the inverted format. The study is based on a post-modern perspective that integrates the educational and instrumental dimensions of the language teaching/learning process bearing in mind that additional/foreign language (L2) teaching ideally conciliates formal aspects of language with the development of critical education. The literature reviewed includes blended learning approaches in general and the Inverted CLIL approach in particular; webquests and principles of language educaction for teaching/learning English as L2. The research question is: How may the blended learning and the Inverted CLIL approaches implemented through webquests foster language education development? The study uses a mixed methods design and fits into the category of development methodology. Data includes questionnaires with pre-service teachers of English as L2 and four webquests produced by them during their Practicum Course. The analysis aimed to verify the potential of the webquest methodology for implementing blended learning and the Inverted CLIL approaches and how these approaches could foster language education development. Overall, the results of the study showed that pre-service teachers tend to prefer traditional format classes and the teaching of linguistic forms at the expense of problematizing social issues, although there is an attempt to critically address these issues in comparison with how they are approached in the National Curriculum Guidelines. The study concludes that the blended learning approach and the Inverted CLIL implemented through the webquests analyzed partially foster language education development.